Clinical Characteristics of Premenstrual Syndrome/Premenstrual Dysphoric Disorder Co-Morbid with Panic Disorder and the Effectiveness of Selective Serotonin Reuptake Inhibitors in Its Treatment - Rossitza Iakimova; Daniil Aptalidis; Milena Pandova; Maria Stoyanova; Maya Stoimenova-Popova (Journal of Biomedical & Clinical Research, 2019)
Premenstrual syndrome (PMS) is often co-morbid with panic disorder (PD). Selective serotonin reuptake inhibitors (SSRis) are the first-line treatment for both PMS and PD when they manifest separately, but their co-occurrence often complicates the treatment. Our objectives were to evaluate the clinical picture of PMS, co-morbid with PD and the way it changes under 6-month SSRI treatment course. For that purpose, we conducted a longitudinal interventional study. We examined 30 women suffering from PMS and a current episode of PD, verified through premenstrual screening tool (PSST) and Mini International Neuropsychiatric Interview (M.I.N.I.6.0.), respectively. Before treatment initiation, irritability, mood lability, anxiety, breast tension and tenderness, changes in appetite, headaches, palpitations, and abdominal bloating were most common. The somatic symptoms were more than twice as common as the psychological. After 6 months of treatment, most of the symptoms mentioned above were still present but less severe. Forty per cent of the women recovered completely. It seems that in cases of comorbidity between PMS and PD, though somatic symptoms are more common, SSRIs are an effective option for managing both somatic and psychological symptoms.